Moral Education in the Book ArRahīqu AlMakhtūm by Shakh Shafy Al-Rahmān AlMubārakfūrī - Wathoni, Lalu Muhammad Nurul; Nursyamsu, Nursyamsu (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Because the world's atmosphere recently has deep moral instability, the desire to reach the century of ethics instead becomes a century of minus ethics. Even though the Islamic ummah has a role model in terms of ethics and morals, namely the figure of the Prophet Muhammad SAW, it becomes a necessity for every Muslim to know him through Shirah An-Nabawiyah, which is beautifully explained in the monumental writing Ar-Rahīqu Al-Makhtūm by the great scholar Syakh Shafy AlRahmān AlMubārakfūrī. The purpose of this study is to examine how Rasulullah SAW developed the thought of moral education contained in the book Ar-Rahīqu Al-Makhtūm by Sheikh Shafy Al-Rahmān Al-Mubārakfūrī. The method used in this study is the library research method with documentation techniques, while the analysis uses content analysis and historical analysis. The results of the study show that there is a moral education that the Prophet SAW developed in the book Ar-Rahīqu Al-Makhtūm by Syekh Shafy Al-Rahmān Al-Mubārakfūrī, namely Rabbāniyah, Insāniyah, and Syumūliyah. The Rabbāniyah or religious dimension is by maintaining human relations with God, namely reviving faith and enlivening makhdhah worship. The Insāniyah dimension includes honesty (shiddiq), responsibility, discipline, hard work, creativity/innovation, independence (i'timad), curiosity (research), and reading/literacy. While Syumuliyah: achievement, democracy, social concern, friendship/loyal friends. Of the three aspects of moral education, the Rabbāniyah dimension is the most dominant of the other dimensions, showing that the human relationship with God is the top priority.